The Israel-Palestine Conflict: Unpacking Ideological and Political Beliefs in Donald Trump’s Recent Speech - Jamshaid, Saima; Tarar, Hafiz Qasim Nisar (Annals of Human and Social Sciences, 2025)
This study intends to analyze the ideological and political dimensions present in the recent speech delivered by Donald Trump, the newly elected President of the United States, concerning the ongoing situation between Israel and Palestine. The basic purpose of the study is to investigate the underlying ideological and political beliefs of Trump reflected from the linguistic choices of the leader. The primary data consists of Trump’s speech, retrieved from the online platform YouTube. A descriptive qualitative approach is employed to capture the ideological elements within the speech. For data analysis, the study utilizes Van Dijk’s (1980) Three-Dimensional Framework, which is particularly suited for exploring ideological representation. The findings reveal that Trump employs assertive language to project authority and influence, condemns the terrorist group Hamas, and affirms the United States’ commitment to defending the State of Israel and the Jewish people. Hopefully, this study is a foundational piece for those exploring political linguistics, ideological discourse, and the rhetorical construction of international policy narratives.